Efeitos da frequência lexical na interpretação de situação-problema em matemática - Agostini, Tainara Duro (Universidade Federal de São Carlos, 2024)
The objective of this study is to investigate the linguistic factors that influence the difficulty in interpreting math word problems faced by students from 6th to 9th grade. This inquiry is necessary because, to reach a solution or understanding of a mathematical text, especially exercises, it is essential to read and comprehend. In other words, there is a process of translating from natural language to mathematical language, an exchange of codes. However, due to the use of words unfamiliar to the students in the composition of word problems, they encounter difficulties in solving them. In this context, we observe that vocabulary is indeed important, as the student needs to know the linguistic object they are dealing with to enable the translation from natural language to mathematical language. Based on the hypothesis that a lack of vocabulary knowledge might affect interpretation, we constructed a corpus of word problem texts to analyze word choice and usage, aiming to determine which words are being used and their frequency to investigate whether the choice of these words influences the student's interpretative process. To assess the frequency of these terms, we performed a comparative analysis between different corpora: word problems, frequent words for Brazilian children, and common terms for adults. After working with the corpora, we developed an experiment to test students' familiarity with the words in the mathematics book and then to see if they could place the word within the context of the statement. This led us to confirm that indeed unfamiliar words hinder students' interpretative processes, indicating that lexical choice is a significant challenge that affects students' interpretative process and academic performance.
Effects of lexical frequency on the interpretation of story problem in mathematics
Keywords: Interface linguagem-matemática; Escolha lexical; Frequência de palavras; LINGUISTICA, LETRAS E ARTES::LINGUISTICA